THE ROLE OF PRESCHOOL EDUCATION IN THE SYSTEM OF PHYSICAL EDUCATION - Eshpulatov Jamshid (Journals Park Publishing, 2023)
This article examines the importance of physical education in preschool institutions in our country. The tasks of physical education in preschool institutions are highlighted.
Keywords: physical education, physical training, preschool education, education, upbringing, health improvement, task, training, exercise.